2008
DOI: 10.1098/rstb.2008.0001
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of Early Stone Age toolmaking: technology, language and cognition in human evolution

Abstract: Archaeological and palaeontological evidence from the Early Stone Age (ESA) documents parallel trends of brain expansion and technological elaboration in human evolution over a period of more than 2 Myr. However, the relationship between these defining trends remains controversial and poorly understood. Here, we present results from a positron emission tomography study of functional brain activation during experimental ESA (Oldowan and Acheulean) toolmaking by expert subjects. Together with a previous study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
307
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(337 citation statements)
references
References 52 publications
24
307
2
4
Order By: Relevance
“…Tool-use abilities also constitute one of the most easily identifiable points at which neuroscience and archaeology meet, given that it is now possible using the new brain imaging methods to explore their neurological foundation in the modern human brain. In this context, Stout et al (2008) present important new results from a PET study during experimental stone toolmaking, which support a coevolutionary hypothesis linking the emergence of language and toolmaking. In particular, their imaging data show that neural circuits supporting stone toolmaking partially overlap with language circuits, which suggests that these behaviours share a foundation in more general human capacities for complex, goal-directed action and are likely to have evolved in a mutually reinforcing way.…”
supporting
confidence: 57%
“…Tool-use abilities also constitute one of the most easily identifiable points at which neuroscience and archaeology meet, given that it is now possible using the new brain imaging methods to explore their neurological foundation in the modern human brain. In this context, Stout et al (2008) present important new results from a PET study during experimental stone toolmaking, which support a coevolutionary hypothesis linking the emergence of language and toolmaking. In particular, their imaging data show that neural circuits supporting stone toolmaking partially overlap with language circuits, which suggests that these behaviours share a foundation in more general human capacities for complex, goal-directed action and are likely to have evolved in a mutually reinforcing way.…”
supporting
confidence: 57%
“…Given the high cognitive demands associated with stone tool production techniques, a great deal of this attention has been focused on how the lithic archaeological record may inform our understanding of the evolution of human cognitive capabilities (Beaune et al, 2009;Gamble et al, 2014). These capabilities include the evolution of language, imitation, complex technological capabilities, increased brain size, complex social systems, cognitive and manual lateralisation, spatial cognition and shape recognition (Ambrose, 2010;de Beaune, 2004;Gowlett et al, 2012;Morgan et al, 2015;Schillinger et al, 2015;Stout, 2011;Stout et al, 2008;Uomini and Meyer, 2013;Wynn, 2002). Comparatively little work has investigated how lithic artefacts may be used to further our understanding of the evolution of human musculoskeletal anatomy and biomechanical capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Language centers are activated for the purpose of "inner-speech" to make the thoughts that are required to complete all manner of tasks more tangible. Stout et al (2008), for instance, demonstrated that the language centers were active when participants were instructed to make complex tools. D's expectation that the language centers should be activated entirely independently from the rest of the brain seems unrealistic.…”
Section: Neuroscience Of Languagementioning
confidence: 99%
“…These latter more complex structured artifacts may well reflect the presence of some kind of "inner speech". Indeed, Stout et al (2008) showed that the act of making such stone tools engages the main language centers of the brain, namely the left inferior frontal gyrus and the superior temporal gyrus.…”
Section: Evolution Of Languagementioning
confidence: 99%